Natural soil biotin application activates soil beneficial microorganisms to improve the thermotolerance of Chinese cabbage - Teng, Zhiyan; Chen, Caizhi; Pan, Kexuan; Liu, Dandan; Yao, Xiangtan; Bai, Songhua; Ni, Jinzhuang; Shao, Yujing; Gu, Zaiyuan; Huang, Li; Chen, Yunwen (Frontiers in Microbiology, 2024)
Chinese cabbage (Brassica campestris L. syn. B. rapa) is a globally cultivated leafy vegetable. However, its annual production is frequently hindered by high-temperature stress, resulting in significant reductions in both plant weight and quality. To address this issue, the efficacy of a novel biofertilizer product, natural soil biotin (NSB), which boasts a rich composition of diverse organic matter-degrading enzymes, was investigated in the study. The present study examined the relatively comprehensive impacts of NSB application on crop yield, growth, nutrient use efficiency, agricultural product quality, and safety. The incorporation of NSB into the soil was accompanied by an increase in Oleomycetes, which induced a decrease in the population abundance and diversity of fungi in the rhizosphere soil. This, in turn, promoted the growth of Chinese cabbage and reduced the relative abundance of harmful fungi, ultimately leading to improved plant weight and quality by creating a more favorable growth environment. Additionally, NSB mitigated the degree of lipid peroxidation in the leaves of Chinese cabbage by enhancing antioxidant enzyme activity and osmoregulatory substance content when exposed to high temperatures (40°C/30°C, 16 h/8 h, 24 h). Overall, this study presents a novel approach to the environmentally friendly cultivation of Chinese cabbage in high-temperature seasons, thereby helping to improve the adaptation strategies of vegetable production to climate change and soil degradation and achieve sustainable horticulture.